2021
DOI: 10.3390/pharmaceutics13122201
|View full text |Cite
|
Sign up to set email alerts
|

The TKI Era in Chronic Leukemias

Abstract: Tyrosine kinases are proteins involved in physiological cell functions including proliferation, differentiation, and survival. However, the dysregulation of tyrosine kinase pathways occurs in malignancy, including hematological leukemias such as chronic myeloid leukemia (CML) and chronic lymphocytic leukemia (CLL). Particularly, the fusion oncoprotein BCR-ABL1 in CML and the B-cell receptor (BCR) signaling pathway in CLL are critical for leukemogenesis. Therapeutic management of these two hematological conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 131 publications
(137 reference statements)
1
6
0
Order By: Relevance
“…As previously reported, GNF-7 functions as a BCR-ABL inhibitor that can overcome the "gatekeeper" BCR-ABL/T315I mutation that resistant to tyrosine kinase inhibitors (TKIs) [16]. Indeed, GNF-7 potently inhibited the proliferation of BCR-ABL/T315I expressing BaF3 cells that resistant to the BCR-ABL inhibitors imatinib and dasatinib (Figure S1A-C) [17]. Interestingly, we found that GNF-7 showed potent anti-proliferation on Ba/F3 cells stably express FLT3-ITD, whereas TKIs such as imatinib and dasatinib exhibited no signi cant proliferation inhibition (Figure S2).…”
Section: Gnf-7 Selectively Inhibits the Proliferation Of Flt3-itd Aml...supporting
confidence: 64%
“…As previously reported, GNF-7 functions as a BCR-ABL inhibitor that can overcome the "gatekeeper" BCR-ABL/T315I mutation that resistant to tyrosine kinase inhibitors (TKIs) [16]. Indeed, GNF-7 potently inhibited the proliferation of BCR-ABL/T315I expressing BaF3 cells that resistant to the BCR-ABL inhibitors imatinib and dasatinib (Figure S1A-C) [17]. Interestingly, we found that GNF-7 showed potent anti-proliferation on Ba/F3 cells stably express FLT3-ITD, whereas TKIs such as imatinib and dasatinib exhibited no signi cant proliferation inhibition (Figure S2).…”
Section: Gnf-7 Selectively Inhibits the Proliferation Of Flt3-itd Aml...supporting
confidence: 64%
“…Furthermore, high-cytogenetic-risk diseases are much more effectively treated with tyrosine kinase inhibitors. Several trials with patients with CML have already shown that in predetermined conditions (CMR for at least 2 years after ≥3 years of TKI treatment), the production of BCR::ABL1 inhibitor can be discontinued and rechallenged in the case of molecular relapse [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The course of the disease in adults is usually milder compared to children and adolescents [ 25 ]. The long-term treatment of CML for pediatric patients is analogous to therapy for adults, and it involves tyrosine kinases inhibitors (TKI): first-generation TKI: Imatinib, second-generation: Dasatinib, Nilotinib and third-generation such asBosutinib [ 26 ]. However, all clinical evidence indicates that a continued search for unique therapy guidelines adapted for children is required.…”
Section: Chronic Myeloid Leukemia (Cml)mentioning
confidence: 99%
“…Classic Hodgkin Lymphoma is divided into four subtypes: lymphocyte-rich CHL, lymphocyte-depleted CHL, mixed cellularity CHL, and nodular sclerosis CHL. HL is the most commonly diagnosed cancer in adolescents (aged 15–19 years) [ 26 ]. For children aged 0–14 years, HL represents 4% of all children's cancers.…”
Section: Hodgkin’s Lymphoma (Hd)mentioning
confidence: 99%